The effect of genetic polymorphism of cytochrome enzymes on metamizole metabolism (مجلة البيان العلمية, 2022)
Two formerly very frequently used analgesic drugs or active metabolites of analgesic drugs, namely 4-methylaminoantipyrine (derived from metamizole) and 4-dimethylaminoantipyrine (also termed antipyrine) were studied here concerning the specific enzymes involved in their oxidative biotransformation by genetically polymorphic and non-polymorphic enzymes. The main conclusions from this investigationare:In vitro metabolism of methylaminoantipyrine to 4-aminoantipyrine was characterized by a KM of 20.9 µmol/l and a Vmax of 58.5 pmol/mg/min in rat liver microsomes (1.25 mg/ml protein). Strongest inhibition of methylaminoantipyrine demethylation in rat liver microsomes was achieved with omeprazole with an IC50 of 0.05 mMIn human liver microsomes, mean KM and Vmax were 251 µmol/l and 144 pmol/mg/min, respectively (2.5 mg/ml protein). Strong inhibition of these reactions was abserved after co-incubation with omeprazole (CYP2C19), fluvoxamine (CYP2C19 and CYP1A2), and tranylcypromine (CYP2C19) with IC50 values of 0.07, 0.07 and 0.18 mmol/l, respectively.Some formation of 4-aminoantipyrine from methylaminoantipyrine was observed in the incubations with recombinant CYP2C19, CYP2D6, CYP1A2, CYP2C8, CYP2A6, CYP1A1, CYP1B1, CYP3A4, CYP3A5, CYP3A7, CYP2C9 and CYP2E1 but the highest formation observed only with CYP2C19 with intrinsic clearances of 0.092 (CYP2C19), 0.027 (CYP2D6), 0.026 (CYP1A2), 0.017 (CYP1A1) and 0.016 (CYP2C8) µl/pmol CYP/min,respectively.With concluded that CYP2C19 is the most important cytochrome P450 enzyme
Keywords: Metamizole; 4-methylaminoantipyrine (4-MAA); 4- aminoantipyrine; metabolism, Human CYP2C19